The Effect of Portable Electrical Motor Trainer Motor Media To Enhancing Creative and Critical Ability - Munawi, Hisbulloh Ahlis; Suwardono, Agus; Indrawati, Elsanda Merita (International Journal for Educational and Vocational Studies, 2020)
The purpose of this study is to determine the effect of using portable electric motor control trainer media on increasing creative thinking skills and critical thinking skills in electrical engineering students. This research is an experimental study using Pretest-Posttest group design. The subject of the study is electrical engineering students at Nusantara University, PGRI Kediri consisting of 27 students. The level of creativity is measured through aspects of fluency, flexibility, authenticity, and elaboration, while aspects of critical thinking ability are by giving simple explanations, building basic skills, giving further explanation, applying strategies and techniques, and concluding. The study determines the increase in creative and critical thinking skills using N-Gain analysis. The result shows that: 1) the students' creative thinking skills are increased by learning using a portable type electric motor control trainer media that was categorized high on aspects of fluency and elaboration, and categorized based on aspects of flexibility and authenticity; 2) the students' critical thinking skills increase after participating in learning by using portable type electric motor control trainer media which is high in the aspects of elementary classification, inference, strategy and tactics, and categorized based on the aspects of basic support and advanced classification.